Formation of Mn-Doped SnO2 Nanoparticles Via the Microwave Technique: Structural, Optical and Electrical Properties. (8th March 2016) - Salah, Numan; Habib, Sami; Azam, Ameer; Ansari, M. Shahnawaze; Al-Shawafi, Waleed M.
Ultrafine pure and Mn-doped SnO2 nanoparticles (NPs) were synthesized via the microwave technique. They were produced using tin chloride and hexamethylenetetramine at the molar ratio of 1:20. The concentrations of Mn in the SnO2 matrix were in the range of 0.1–5 mol%. These nanomaterials were characterized using different techniques. SEM and TEM results show ultrafine NPs with sizes around 10 nm in both pure and Mn-doped samples. A single-phase rutile-type tetragonal structure was observed in pure and Mn-doped samples, as revealed by XRD analysis, while PL emission spectra of these samples showed the broad band peaking at 365 nm. The intensity of this band was observed to increase by increasing the concentration of Mn up to 0.3 mol%, and then to decrease at higher values. A Raman spectrum of the pure sample shows two bands at 630 and 780 cm −1, which are the regular A1g and B2g vibrations of SnO2, while an extra band is observed at 210 cm −1 in the doped samples. The resistivity of Mn-doped SnO2 NPs was observed to decrease by increasing the temperature, but it drastically increased by increasing the Mn content. The activation energy of Mn-doped SnO2 NPs was also calculated, and was found to increase from 0.53 to 1.21 eV by varying the Mn dopant from 0.1 to 5 mol%. These results show that the microwave technique is a powerful tool that can be used to produce a high yield of ultrafine SnO2 NPs. Moreover, Mn was found to be a proper activator for tuning the optical and electrical properties of this material, for its application as a dilute magnetic semiconductor or spintronic devices.